2016
DOI: 10.1088/0953-8984/28/42/426003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rare-earth (Er and Gd) substitution on the magnetic and multiferroic properties of DyFe0.5Cr0.5O3

Abstract: We report the results of our investigations on the influence of partial substitution of Er and Gd for Dy on the magnetic and magnetoelectric properties of DyFe 0.5 Cr 0.5 O 3 , which is known to be a multiferroic system. Magnetic susceptibility and heat capacity data, apart from confirming the occurrence of magnetic transitions at ~ 121 and 13 K in DyFe 0.5 Cr 0.5 O 3 , bring out that the lower transition temperature only is suppressed by rare-earth substitution.Multiferroic behavior is found to persist in Dy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Presence of two magnetic-moment containing transition metal ions in the perovskite structure make such compounds interesting from magnetism angle and its coupled properties. In this article, we focus on DyFe 0.5 Cr 0.5 O 3 [9,10], which has been shown to be a multiferroic, exhibiting significant magnetocaloric effect (MCE) with magnetoelectric (ME) coupling playing a role to enhance MCE [9]. We have recently found that a partial replacement of Dy by some other rare-earth ions leads to the enhancement of both MCE and electric polarization [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of two magnetic-moment containing transition metal ions in the perovskite structure make such compounds interesting from magnetism angle and its coupled properties. In this article, we focus on DyFe 0.5 Cr 0.5 O 3 [9,10], which has been shown to be a multiferroic, exhibiting significant magnetocaloric effect (MCE) with magnetoelectric (ME) coupling playing a role to enhance MCE [9]. We have recently found that a partial replacement of Dy by some other rare-earth ions leads to the enhancement of both MCE and electric polarization [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we focus on DyFe 0.5 Cr 0.5 O 3 [9,10], which has been shown to be a multiferroic, exhibiting significant magnetocaloric effect (MCE) with magnetoelectric (ME) coupling playing a role to enhance MCE [9]. We have recently found that a partial replacement of Dy by some other rare-earth ions leads to the enhancement of both MCE and electric polarization [10]. Such chemical substitutions do not involve any electron or hole doping.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, magnetoelectric multiferroic (ME-MF) materials have attracted considerable attention due to their promising applications in multifunctional devices, such as computer memory, magnetic field sensors, novel spintronic devices, energy harvesting, etc [1][2][3][4]. One such system, namely rare-earth chromites (RCrO 3 ) have been explored widely for their ME-MF properties [5][6][7]. In some recent reports the magnetocaloric effect (MCE), which is mainly characterized by an isothermal magnetic entropy change (ΔS) achieved by adiabatic tuning of the magnetization, have also been investigated in the RCrO 3 system.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it can be considered that T ¼ 11.97 K is the transition temperature that the ions' moment direction from order to disorder, which may correspond to the ordering temperature of Gd-Fe/Cr ferromagnetic exchange. [21,34,35] A second maximum, T ¼ 259.96 K, corresponds to the phase transition temperature T 2 of the superexchange interaction between Fe 3þ -O-Cr 3þ .…”
Section: Temperature Dependence Of Magnetizationmentioning
confidence: 99%